Analisis Isi Pesan Dakwah dalam Novel “Tinta Terakhir” Karya Narandara - Astri Syahputri, Siti Novi; Nurhanifah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The rapid development of technology and communication in this modern era influences the way da'i (preachers) convey da'wah messages to mad'u (listeners or recipients of da'wah). In this case, the use of various da'wah media, such as print, electronic and digital media, is a necessity as well as an effective strategy to attract the attention of mad'u. One effective method for conveying da'wah messages is through print media such as novels. Novels are unique in their literary sentences which are able to compete with other media in terms of popularity and effectiveness in conveying da'wah messages. This research aims to find out the da'wah messages contained in the novel